1937
DOI: 10.1002/hlca.19370200171
|View full text |Cite
|
Sign up to set email alerts
|

Méthode d'analyse de l'ozone très dilué. II. Détermination de la concentration de l'ozone dans l'air à Genève

Abstract: La méthode d'analyse de l'ozone très dilué, basée sur l'action catalytique exercée par l'ozone sur l'oxydation d'une solution d'aldéhyde butyrique dans l'hexane, a conduit, pour la concentration en ozone de l'air à Genève (altitude 400 m.), à la valeur 7 × 10−9± 0,3 × 10−9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1937
1937
1958
1958

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…The remaining reactions of ozone as an oxidant appear to be of the type in which oxygen enters into the reaction and ozone serves primarily as the initiator of the reaction. Briner and coworkers (99,101,105,106,107,109,110,112,113,117,118,119,125,129,130,137,138,139,140,141,142,143,153,217,218,221) have studied extensively the action of ozone on aldehydes. Ozone-oxygen mixtures were found to oxidize benzaldehyde and other aldehydes to a mixture of the corresponding acid and per acid (cf.…”
Section: Groupingsmentioning
confidence: 99%
“…The remaining reactions of ozone as an oxidant appear to be of the type in which oxygen enters into the reaction and ozone serves primarily as the initiator of the reaction. Briner and coworkers (99,101,105,106,107,109,110,112,113,117,118,119,125,129,130,137,138,139,140,141,142,143,153,217,218,221) have studied extensively the action of ozone on aldehydes. Ozone-oxygen mixtures were found to oxidize benzaldehyde and other aldehydes to a mixture of the corresponding acid and per acid (cf.…”
Section: Groupingsmentioning
confidence: 99%
“…It would seem, therefore, that in order to measure a purely thermal rate of oxidation, care must be taken to purify the aldehyde in the absence of air and to remove both catalysts and inhibitors. Most workers (16,17,29,33,39) have found that the purification of the aldehyde decreases the rate of the dark reaction, that is, removes catalysts, while Cooper and Melville (21) found the rate of oxidation of decanal to increase with successive distillation, presumably owing to removal of inhibitor. Mulcahy and Watt (37) observed both effects in several purifications of benzaldehyde when starting with different samples of impure aldehyde.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…The influence of ozone in minute concentrations upon the rate of oxidation has been very thoroughly studied (12)(13)(14)(15)(16)(17)(18)). It appears that in order to measure a purely thermal reaction rate it is necessary to reduce the ozone concentration to less than 1 part in 109 (17).…”
Section: Oxygenmentioning
confidence: 99%
See 1 more Smart Citation
“…Selon Briner (39 ) , « l'accroissement de la fréquence du courant qui produit l'arc, exerce une influence favorable sur les réactions endoénergéti-.ques » ; cette observation a amené l'auteur à appliquer cette méthode expérimentale à l'obtention de l'acétylène à partir du méthane.…”
Section: Introductionunclassified